I just can't help it by mr. tickle: little owl - Hargreaves, Roger (World International London, 1991)
"I Just Can't Help It" is a whimsical story that follows a young character who navigates the challenges of impulse control and self-expression. With vibrant illustrations and relatable scenarios, the protagonist learns to embrace their feelings while discovering the importance of patience and thoughtfulness. Through fun adventures and gentle lessons, this book encourages young readers to understand their emotions and the joy of being themselves, making it an engaging read for children and parents alike.